Seroprevalence epidemiological studies on equine trypanosomosis using Ab-ELISA in a part of semi-arid zone of northern plains of India - SINGH, R K; TRIPATHI, A K; SINGH, S K; SINGH, A P; YADAV, S C (The Indian Journal of Animal Sciences, 2016)
In the present investigation, seroprevalence and host related epidemiological factors of equine trypanosomosis were assessed using Ab-ELISA. Serum samples (515) of equines (horse–227, mule–249 and donkey–39) suspected for trypanosomosis (surra) were collected during April 2014 to March 2015, from 7 districts of semi-arid zones of northern plains of India. Overall seroprevelence of 22.33% was recorded indicating endemicity of surra in equines of the region. Maximum prevalence was recorded in district Mathura (24.81%) followed by Bharatpur (23.26%) and the lowest prevalence was recorded in Hathras (16.23%) district. Trypanosomosis was prevalent throughout the year in the region and higher prevalence was observed in monsoon and post monsoon months followed by winter and least in the summer. Prevalence of trypanosomosis in equines does not vary with the host related factors, viz. sex, age, species, pregnancy status and months of pregnancy in the region.